Pemanfaatan Apikasi Google Maps Sebagai Upaya Branding UMKM Di Desa Singaraja Kabupaten Indramayu - Ulinniam; Hakim , M.Imad Lukmanul; Safitri , Amelia Nurul; Furohman, Arif; Rahmawati , Mudita; Nur’aeni , Leni; Fauzan, M.Abdullah; Liana, Tasya Happy; Asyifa; Risliyanti, Iis Novia; Amaluddin, Doni; Yusuf, M.Azzly Ansori; Nurfaridah, Widia Siti; Trisakia, Ananda; Wulansari (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
Singaraja Village has large MSME potential, but it has not been utilized optimally. One of the obstacles faced by MSMEs is a lack of understanding about digital marketing, especially the use of the Google Maps application. This KKN activity aims to provide education and training to MSMEs in Singaraja Village regarding the importance of branding and how to use Google Maps as a marketing tool. The methods used in this activity are socialization, training and mentoring. MSME players are given an understanding of the concept of branding, the benefits of Google Maps for MSMEs, and how to register their business on Google Maps. Apart from that, they are also taught how to manage business information on Google Maps, such as adding product photos, opening hours and contact information. The results of this activity show that MSMEs in Singaraja Village are enthusiastic about participating in the training and understand the importance of branding for their business. They are also able to register their business on Google Maps and manage business information independently. By registering MSMEs on Google Maps, it is hoped that they can increase the visibility of their businesses, attract more customers, and ultimately increase revenue.